Maize productivity (Diamantes 8843) under different planting densities and potassium doses - Urbina-Briceño, Cesar (2023)
Introduction. Agronomical practices such as plant density and fertilizer doses are necessary to increase corn yield production in rural zones in Costa Rica. Objective. Evaluation of three plant densities and three K2O rate on the yield production in maize variety Los Diamantes 8843 in Guanacaste, Costa Rica. Materials and methods. This study was carried out at the Finca Experimental Santa Cruz (FESC) of the University of Costa Rica, between September – December 2018. 50 000, 57 143, 66 666 plants by a hectare (ha) were evaluated with 0, 70, 140, 210 kg.ha-1 of K2O in a factorial experimental design. There were quantified the plant height, stem thickness, dry biomass, nutrients uptake and grain yield. Also, the physiological efficiency, agronomic efficiency, partial factor productivity, apparent recovery efficiency and internal utilization efficiency were calculated. Results. The highest K2O rates increased the nutrient uptake, while cob quality and yield components did not show statistical differences with the three K2O rate. The lowest plant density exhibited the best agronomic parameter values. However, nutrient uptake, cob quality, and yield component were not affected by plant density. 66 666 plant. ha-1 with 70 kg.ha-1 of K2O had the highest agronomic efficiency index in this experiment. Conclusion. Soils with high K concentration revealed that low rate such as 70 kg.ha-1 of K2O can satisfy the K requirements in Los Diamantes 8843. But, in order to conserve the K concentration in the soil, it is essential to supply 131.7 kg.ha-1 of K to provide a good plant uptake requirement without decrease the K concentration in the FESC soil.